DIASTEMA CORRECTION OF PERIODONTAL DISEASES FOLLOWING PERIODONTAL THERAPY ALONE - Hartanti Hartanti (Universitas Baiturrahmah, 2021)
Introduction: An acquired diastema may be a warning sign signaling advanced periodontitis. Gingival inflammation, reduced bony support, and tooth mobility may contribute to the drifting of teeth, a condition called pathologic tooth migration, and formed tooth gap or space between two teeth or more. Identification of the causative factors involved in pathologic tooth migration is crucial for successful treatment. Case and Management: Case 1 - A 38-year-old woman reported to the Department of Periodontics with the chief complaint of bleeding gums. An intraoral examination revealed highly inflamed periodontal tissue with heavy plaque and calculus deposition. And in case 2 - A 34-year-old woman had a chief complaint of an increasing gap between her maxillary anterior teeth. After clinical and radiographic examinations, the patient was diagnosed with chronic periodontitis and gingival enlargement, pathological tooth migration with diastema. In Case 1, the patient was performed scaling, root planning, and curettage. Re-evaluation after 1 month revealed the reduction of visible inflammation and persistence of pockets and complete closure of spacing between the lower incisive. In case 2, the patient was performed scaling, and gingivectomy, and gingivoplasty. Re- evaluation after 3 months there is a complete closure of spacing between the upper incisors. Conclusion: These cases indicate that migrated teeth sometimes return to their original positions after the etiologic factor has been eliminated such as gingival inflammation, attachment loss, gingival overgrowth